Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s40520-020-01751-5
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned hospital transfers from nursing homes: who is involved in the transfer decision? Results from the HOMERN study

Abstract: Background Emergency department visits and hospital admissions are common among nursing home residents (NHRs) and seem to be higher in Germany than in other countries. Yet, research on characteristics of transfers and involved persons in the transfer decision is scarce. Aims The aim of this study was to analyze the characteristics of hospital transfers from nursing homes (NHs) focused on contacts to physicians, family members and legal guardians prior to a transfer. Methods We conducted a multi-center study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
1
16
0
1
Order By: Relevance
“…Although treatment options by phone (e.g., between GPs and nursing home residents or the residents' relatives or care nurses) are limited, our study further shows that residents have almost five telephone contacts with GPs per year. Given this finding, and given the expected importance of telephone contacts during a pandemic and in emergency cases [21,22], the importance of telephone contacts is probably greater than expected. Future studies should therefore systematically investigate the role of telephone contacts in the provision of medical care in nursing homes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although treatment options by phone (e.g., between GPs and nursing home residents or the residents' relatives or care nurses) are limited, our study further shows that residents have almost five telephone contacts with GPs per year. Given this finding, and given the expected importance of telephone contacts during a pandemic and in emergency cases [21,22], the importance of telephone contacts is probably greater than expected. Future studies should therefore systematically investigate the role of telephone contacts in the provision of medical care in nursing homes.…”
Section: Discussionmentioning
confidence: 98%
“…However, in order to draw a complete picture of medical care provision in this setting, it is also necessary to know the number of consultations (i.e., the intensity of medical care) and whether these take place in the nursing home, at a practice, or by telephone. All types of contacts can be relevant for the medical care process (e.g., telephone contacts with GPs during a pandemic and prior to unplanned hospital stays [21,22]). However, previous studies focused particularly on proportions of nursing homes and nursing home residents having contact with physicians [8,10,11,13] but did not systematically investigate the number and types of contact.…”
Section: Introductionmentioning
confidence: 99%
“…In emergency situations, the involvement of relatives is mainly limited to decision making, emergency management and advocacy (23). Nurses try to inform relatives about emergencies as quickly as possible, in order to encourage their involvement from an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NH staff was asked if the resident was carrying an advance directive (AD) and stated the details by adjusting the emergency advance directive called the patient directive for life sustaining measures (PALMA) [17]. Further information about the decision-making process (final decision maker, previous contact with other health care specialists) and the respective transfer (date and time slot) were gathered and have been published in detail elsewhere [13].…”
Section: Data Collection and Assessed Variablesmentioning
confidence: 99%
“…However, little is known about the underlying pathways that led to the transfer decision and the extent of treatment in ED in those not being hospitalized. Recent data suggests that in two-thirds of the transfers the GP was not involved in the decision making [ 13 ]. Burke et al found that 19.0% of the NHR discharged from the ED did not have any diagnostic testing prior [ 11 ].…”
Section: Introductionmentioning
confidence: 99%